ZnO nanoparticles and zeolite influence soil nutrient availability but do not affect herbage nitrogen uptake from biogas slurry. (February 2019) - Aziz, Yasir; Shah, Ghulam Abbas; Rashid, Muhammad Imtiaz
Abstract: Recently, there is a growing interest among agriculturists to use nanotechnology for the development of nutrient-use efficient fertilizers. However, its sustainable use for the synthesis of mineral or organic nano-fertilizers requires a thoughtful of the mechanism as well as the fate of nutrients and their interaction with soil-plant systems. Therefore, the aim of current study was to investigate the mixing of three different application rates of zinc oxide nanoparticles (ZNPs: 1.4, 2.8 and 3.6 mg kg −1 soil) as well as zeolite (141, 282 and 423 mg kg −1 soil) with biogas slurry (AS) on soil nutrient availability and herbage nitrogen (N) and zinc (Zn) uptake in a standard pot experiment. We found that both ZNPs and zeolite significantly increased mineral N content in soil compared to AS alone (P < 0.05). On the other hand, plant available phosphorus or potassium and microbial biomass carbon (C) in the soil were neither significantly affected by any application rate of ZNPs nor zeolite mixed AS. Soil microbial biomass N was significantly higher in second and third application rates of both ZNPs and zeolite amended AS treatments compared to AS alone. However, this increment in mineral N did not influence shoot uptake and herbage apparent recovery of this nutrient from AS. Similarly, co-mixing of both ZNPs and zeolite in AS did not influence shoot N uptake but Zn uptake was significantly higher in this treatment compared to AS alone. Therefore, this combination would be considered for improving crop Zn uptake under such fertilizer management regimes. Graphical abstract: Highlights: ZnO nanoparticles (ZNPs) and zeolite mixed biogas slurry (AS) tested against ryegrass. ZNPs mixed AS increased mineral nitrogen (N) content in the soil. Microbial biomass N was also increased by AS mixed with ZNPs and zeolite. ZNPs and zeolite did not influence grass dry matter yield and N uptake. Co-mixing ZNPs and zeolite in AS enhanced grass Zn uptake.